The chromosome‐scale genomes of Dipterocarpus turbinatus and Hopea hainanensis (Dipterocarpaceae) provide insights into fragrant oleoresin biosynthesis and hardwood formation. Issue 3 (15th December 2021) - Wang, Sibo; Liang, Hongping; Wang, Hongli; Li, Linzhou; Xu, Yan; Liu, Yang; Liu, Min; Wei, Jinpu; Ma, Tao; Le, Cheng; Yang, Jinlong; He, Chengzhong; et al.
Summary: Dipterocarpaceae are typical tropical plants (dipterocarp forests) that are famous for their high economic value because of their production of fragrant oleoresins, top‐quality timber and usage in traditional Chinese medicine. Currently, the lack of Dipterocarpaceae genomes has been a limiting factor to decipher the fragrant oleoresin biosynthesis and gain evolutionary insights into high‐quality wood formation in Dipterocarpaceae. We generated chromosome‐level genome assemblies for two representative Dipterocarpaceae species viz . Dipterocarpus turbinatus Gaertn. f. and Hopea hainanensis Merr. et Chun. Our whole‐genome duplication (WGD) analysis revealed that Dipterocarpaceae underwent a shared WGD event, which showed significant impacts on increased copy numbers of genes related to the biosynthesis of terpene, BAHD acyltransferases, fatty acid and benzenoid/phenylpropanoid, which probably confer to the formation of their characteristic fragrant oleoresin. Additionally, compared with common soft wood plants, the expansion of gene families was also found to be associated with wood formation, such as in CESA (cellulose synthase), CSLE (cellulose synthase‐like protein E), laccase and peroxidase in Dipterocarpaceae genomes, which might also contribute to the formation of harder, stronger and high‐density timbers. Finally, an integrative analysis on a combination of genomic, transcriptomic and metabolic data from different tissues provided further insights into the molecular basis of fragrant oleoresins biosynthesis and high‐quality wood formation of Dipterocarpaceae. Our study contributes the first two representative genomes for Dipterocarpaceae, which are valuable genetic resources for further researches on the fragrant oleoresins and superior‐quality timber, genome‐assisted breeding and improvement, and conservation biology of this family.